PENGARUH BERBAGAI INTENSITAS NAUNGAN TERHADAP PERTUMBUHAN SEMAI EBONI (Diospyros celebica Bakh.) - Asriyanti, Asriyanti; Wardah, Wardah; Irmasari, Irmasari (Universitas Tadulako, 2015)
Eboni (Diospyros celebica Bakh.) is a semi-toleranttree species that need shading during growth process. This study aimed todetermine the effect of various intensity of shading on the growth of eboni seedlings.The researchwas conducted from May to August 2013, at thePermanentNursery,Tadulako University, Palu,CentralSulawesi. The experiment was laid out in a Randomized Block Design (RBD) with five treatments; shading percentage 10% (N1), shading percentage 30% (N2), shading percentage 50% (N3), shading percentage 70% (N4) and shading percentage 90% (N5). Observation Parameters consist of seedling height increment, stem diameter increment, and increment of leaf number per plant, root fresh and dry weight, and shoot fresh and dry weight. The results of the study showed that there were no significant differences between the treatments in all the parameters assessed. The height increment response and root fresh and dry weight of eboni seedlings was higher in the treatment with shading 90% than other shading intensity treatments, while the diameter and leaf number increment response and shoot fresh and dry weight was higher in the treatment with shading 30%. Keywords : Shading intensity, Growth, Diospyros celebica Bakh.